Model checking ontology‐driven reasoning agents using strategy and abstraction. (7th April 2019) - Rakib, Abdur; Faruqui, Rokan Uddin
Summary: We present a framework for the modelling, specification, and verification of ontology‐driven multi‐agent rule‐based systems (MASs). We assume that each agent executes in a separate process and that they communicate via message passing. The proposed approach makes use of abstract specifications to model the behaviour of some of the agents in the system and exploits information about the reasoning strategy adopted by the agents. Abstract specifications are given as Linear Temporal Logic (LTL) formulas which describe the external behaviour of the agents, allowing their temporal behaviour to be compactly modelled. Both abstraction and strategy have been combined in an automated model checking encoding tool T ovrba for rule‐based multi‐agent systems which allows the system designer to specify information about agents' interaction, behaviour, and execution strategy at different levels of abstraction. The T ovrba tool generates an encoding of the system for the Maude LTL model checker, allowing properties of the system to be verified.